Spatial distributions of macrozoobenthic community and environmental condition of the Manfredonia Gulf (South Adriatic, Mediterranean Sea, Italy). Issue 1 (13th December 2018) - Scirocco, T.; Cilenti, L.; Specchiulli, A.; Pelosi, S.; D'Adamo, R.; Urbano, F.
No abstract available